Socioeconomic status and subclinical coronary disease in the Whitehall II epidemiological study. - Andrew Steptoe; Mark Hamer; Katie O'Donnell; Shreenidhi Venuraju; Michael G Marmot; Avijit Lahiri (PLoS ONE)
Background There are pronounced socioeconomic disparities in coronary heart disease, but the extent to which these primarily reflect gradients in underlying coronary artery disease severity or in the clinical manifestation of advanced disease is uncertain. We measured the relationship between socioeconomic status (SES) as indexed by grade of employment and coronary artery calcification (CAC) in the Whitehall II epidemiological cohort, and tested the contribution of lifestyle, biological and psychosocial factors in accounting for this association. Methods and findings CAC was assessed in 528 asymptomatic men and women aged 53-76 years, stratified into higher, intermediate and lower by grade of employment groups. Lifestyle (smoking, body mass index, alcohol consumption, physical activity), biological (blood pressure, lipids, fasting glucose, inflammatory markers) and psychosocial factors (work stress, financial strain, social support, depression, hostility, optimism) were also measured. Detectable CAC was present in 293 participants (55.5%). The presence of calcification was related to lifestyle and biological risk factors, but not to grade of employment. But among individuals with detectable calcification, the severity of CAC was inversely associated with grade of employment (p = 0.010), and this relationship remained after controlling for demographic, lifestyle, biological and psychosocial factors. Compared with the higher grade group, there was a mean increase in log Agatston scores of 0.783 (95% C.I. 0.265-1.302, p = 0.003) in the intermediate and 0.941 (C.I. 0.226-1.657, p = 0.010) in the lower grade of employment groups, after adjustment for demographic, lifestyle, biological and psychosocial factors. Conclusions Low grade of employment did not predict the presence of calcification in this cohort, but was related to the severity of CAC. These findings suggest that lower SES may be particularly relevant at advanced stages of subclinical coronary artery disease, when calcification has developed.